Quercetin as an antiviral weapon-A review - Kalita, Ramen; Bhattacharya, Kunal; Ali, Amir; Sandilya, Satyasish (Journal of Applied Pharmaceutical Research, 2021)
Antioxidants are substances that can prevent cells from the damage caused by unstable molecules such as free radicals. Quercetin, a plant pigment present in many fruits, vegetables, grains, and one of the most beneficial antioxidants in the diet and plays an important role in helping the body and prevent free radical damage, which is linked to chronic diseases. The antioxidant properties of quercetin may help to reduce inflammation, allergy symptoms, blood pressure. A lot of studies have been done and experiments have been conducted both in vivo and in vitro and it has been found that in cultured cells many respiratory viruses were inhibited by quercetin. At a minimal inhibitory concentration of 0.03 to 0.5μg/ml in WI-38 or Hela cells, Cytopathic effects produced by echovirus type 7,11,12,19, rhinovirus, poliovirus, and coxsackievirus A21 and B1 were inhibited. The plaque formed by DNA and RNA viruses such as Herpes Simplex Virus-1, Polio type 1, and parainfluenza types 3 were effectively reduced demonstrating its anti-replicative properties. This article reviews effect of quercetin on different types of viral infections.